2015
DOI: 10.1177/0098628315587617
|View full text |Cite
|
Sign up to set email alerts
|

Learning the Brain in Introductory Psychology

Abstract: The goal of this research was to determine whether there is a generation effect for learner-created keyword mnemonics and real-life examples, compared to instructor-provided materials, when learning neurophysiological terms and definitions in introductory psychology. Students participated in an individual (Study 1) or small-group (Study 2) in-class activity during which they used three strategies: generate new keyword mnemonics, generate new real-life examples, and read instructor-provided mnemonics and exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Dunlosky et al (2013) concluded from their extensive review that practice testing is extremely effective for longer-term learning in a variety of learning situations. We also note that testing is one example of a broader category of memory strategy called generation , which is based on the idea that memory is better for learner-created materials than instructor/trainer-created ones (e.g., Slamecka & Graf, 1978; for more on generation in relation to educationally relevant materials, see McCabe, 2015).…”
Section: Learning Strategies From Applied Memory Researchmentioning
confidence: 99%
“…Dunlosky et al (2013) concluded from their extensive review that practice testing is extremely effective for longer-term learning in a variety of learning situations. We also note that testing is one example of a broader category of memory strategy called generation , which is based on the idea that memory is better for learner-created materials than instructor/trainer-created ones (e.g., Slamecka & Graf, 1978; for more on generation in relation to educationally relevant materials, see McCabe, 2015).…”
Section: Learning Strategies From Applied Memory Researchmentioning
confidence: 99%
“…This hypothesis is reminiscent of those explored in developmental studies of generalization and causal reasoning (Gopnik, 2000(Gopnik, , 2001. Research on learning and memory suggests that self-generated knowledge and autonomous learning are conducive to the encoding of information and its later retrieval in novel situations (e.g., Deci & Ryan, 2008;MacLeod et al, 2012;McCabe, 2015).…”
Section: Future Directionsmentioning
confidence: 88%
“…Autocatalytic networks have been mathematically extended and generalized as Reflexively Autocatalytic Foodset Generated networks (RAFs) (Hordijk, Hein & Steel, 2010;Hordijk, Kauffman & Steel, 2011;Hordijk & Steel, 2004, 2015, 2016Steel, Hordijk, & Xavier, 2019;Steel, Xavier & Huson, 2020;Xavier, et al, 2020). The RAF framework stimulated a flurry of new applications of the autocatalytic networks framework to cognition and cultural evolution (Gabora, Beckage & Steel, 2022;Gabora & Steel, 2017, 2020a,b, 2021Ganesh & Gabora, 2022a,b).…”
Section: Autocatalytic Network: Identifying What Lies Beyond the Natu...mentioning
confidence: 99%
“…This type of demonstration is both feasible and manageable for students and could thus facilitate their learning (Howard & Michael, 2019). Furthermore, this handson experience could facilitate mnemonic strategies for meaningfully organizing and chunking to-be-learned information about the present paradigm (McCabe, 2015). This approach should assist with increasing students' understanding of feedback processing, thus improving their receptivity to what is generally accepted as a difficult component of learning psychology.…”
Section: Discussionmentioning
confidence: 99%